If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) = -9 Reorder the terms: 3(5 + x) = -9 (5 * 3 + x * 3) = -9 (15 + 3x) = -9 Solving 15 + 3x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 3x = -9 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = -9 + -15 3x = -9 + -15 Combine like terms: -9 + -15 = -24 3x = -24 Divide each side by '3'. x = -8 Simplifying x = -8
| 124-p=628 | | (Y-25)+x=180 | | X^2=11-x | | 12(3x-4)=3(12x+2) | | -4x^2-9x-6=0 | | -(6x-4)=-4(x+6) | | (4+2n^3)+(5n^3+2)=0 | | -(7y+3)-(-6y-4)=-3 | | 3+3m-1=9m+6-5m | | 3(5X+4)-10X+9=51 | | 17+3y=5 | | Y-25=180 | | -2(x-8)+9=25 | | Y-25+x+52+96=360 | | -5-3b=4(b+4) | | x+2x+4=10 | | X+52+96=180 | | 26-2a=-2(6a+3)+2 | | y=1.5x-0.4 | | 4(2x+1)-3x=34 | | 3s+8=-9s | | 5x^5=20x^3 | | 2x^2-15x+27=0 | | 4x+2*8=9*4x | | -2(7r+1)-6=-64 | | 2x^2-7x+9=x+1 | | -7.5x=15.0 | | -36=-v+8(v-8) | | 5y=10x-15 | | 162=6x+6(x+7) | | x^2-18x+70=0 | | 6x-7y=49 |